PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN DI SELURUH PROVINSI INDONESIA - Simbolon, Henny Agnecia Uliarta; Kurniawan, Christophorus Heni (Modus Journals, 2018)
The accountability of the local government to the community can be demonstrated through the Financial Statements of Local Government (Laporan Keuangan Pemerintah Daerah/LKPD). Financial Statements are basically the result of an accounting process that can be used as a communication tool between a company with parties who interested to the company activities (Munawir, 2004). Presenting the Financial Statements of Local Government based on Government Accounting Standards (Standar Akuntansi Pemerintahan/SAP) is one concrete effort that can realized a clean and responsible government. This study was conducted to examine the effect of local government size, legislative size, local government wealth, intergovernmental revenue, administrative age, functional differentiation, job specialization and financial independence ratio to the level of financial statement disclosure throughout the Province of Indonesia.The sample used in this study is the Financial Statements of Local Government throughout the Province of Indonesia in 2013-2015. Sampling technique in this research use purposive sampling. Criteria in sampling of this study is the Financial Statements of Local Governments throughout the Province of Indonesia published from 2013 to 2015 and contains data required as a research variable. Multivariate regression is used to analize data.The results showed that the local government size has a positive effect on the level of financial statement disclosure. Intergovermental revenue and financial independence ratio have a negative effect on level of financial statement disclosure. Legislative size, local government wealth, administrative age, functional differentiation and job specialization have no effect on the level of financial statements disclosure.Â Keywords: Government size, legislative size, local government wealth, intergovernmental revenue, administrative age, functional differentiation, job specialization,financial independence ratio, and financial statement disclosure.